INTEGRATION AND AUTOMATION IN ACTIVE PROTECTION OF NETWORK RESOURCES: PROSPECTS FOR DEVELOPMENT - Daukenov, N.B.; Tereikovskyi, I.A. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2024)
This study examines the future prospects of integration and automation in active defense of network resources. The paper aims to evaluate the effectiveness of integrated and automated network resource defense systems in detecting and responding to cyber threats. Using analysis of existing technologies, attack modeling and defense responses, the study confirms the significance of integration and automation in reducing threat detection time and improving detection accuracy. Object and Subject: The object of the study is integrated and automated defense systems and the subject of the study is their effectiveness in detecting and responding to cyber threats. Objectives: 1. To analyze the existing integration and automation technologies in the field of network resource protection. 2. Conduct simulations of attack scenarios and defense responses to evaluate the effectiveness of integrated defense systems. 3. Examine the impact of integration and automation on threat detection time and threat detection accuracy. Results of the study: - Decrease in threat detection time from 200 minutes to 20 minutes after implementing integration and automation. - Increase in threat detection accuracy from 75% to 95%. - Confirmation of the value of integration and automation in improving cyber threat detection and response. Analysis of the results suggests that integration and automation play a key role in improving the protection of network resources, making systems more responsive and accurate in detecting and preventing cyberattacks.